Impaired pulmonary arterial vasoconstriction and nitric oxide-mediated relaxation underlie severe pulmonary hypertension in the sugen-hypoxia rat model - Christou, Helen; Hudalla, Hannes (The journal of pharmacology and experimental therapeutics, 2018)
Pulmonary vasoreactivity could determine the responsiveness to vasodilators and, in turn, the prognosis of pulmonary hypertension (PH). We hypothesized that pulmonary vasoreactivity is impaired, and we examined the underlying mechanisms in the Sugen-hypoxia rat model of severe PH. Male Sprague-Dawley rats were injected with Sugen (20 mg/kg s.c.) and exposed to hypoxia (9% O2) for 3 weeks, followed by 4 weeks in normoxia (Su/Hx), or treated with Sugen alone (Su) or hypoxia alone (Hx) or neither (Nx). After hemodynamic measurements, the heart was assessed for right ventricular hypertrophy (Fulton’s index); the pulmonary artery, aorta, and mesenteric arteries were isolated for vascular function studies; and contractile markers were measured in pulmonary arteries using quantitative polymerase chain reaction (PCR). Other rats were used for morphometric analysis of pulmonary vascular remodeling. Right ventricular systolic pressure and Fulton’s index were higher in Su/Hx versus Su, Hx, and Nx rats. Pulmonary vascular remodeling was more prominent in Su/Hx versus Nx rats. In pulmonary artery rings, contraction to high KCl (96 mM) was less in Su/Hx versus Nx and Su, and phenylephrine-induced contraction was reduced in Su/Hx versus Nx, Hx, and Su. Acetylcholine (ACh)-induced relaxation was less in Su/Hx versus Nx and Hx, suggesting reduced endothelium-dependent vasodilation. ACh relaxation was inhibited by nitric oxide synthase (NOS) and guanylate cyclase blockade in all groups, suggesting a role of the NO-cGMP pathway. Nitrate/nitrite production in response to ACh was less in Su/Hx versus Nx, supporting reduced endothelial NO production. Sodium nitroprusside (10−8 M) caused less relaxation in Su/Hx versus Nx, Hx, and Su, suggesting a decreased responsiveness of vascular smooth muscle (VSM) to vasodilators. Neither contraction nor relaxation differed in the aorta or mesenteric arteries of all groups. PCR analysis showed decreased expression of contractile markers in pulmonary artery of Su/Hx versus Nx. The reduced responsiveness to vasoconstrictors and NO-mediated vasodilation in the pulmonary, but not systemic, vessels may be an underlying mechanism of severe PH in Su/Hx rats and appears to involve attenuation of the NO relaxation pathway and a switch of pulmonary VSM cells to a synthetic less reactive phenotype.
Gesehen am 14.05.2019